ANALISIS PENERAPAN GERAKAN LITERASI SEKOLAH TERHADAP MINAT BACA PESERTA DIDIK KELAS V SD NEGERI 1 KETANGGA JERAENG - Pebriani, Lina; Syaiful Musaddat; Abdul Kadir Jaelani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to analyze the implementation of the School Literacy Movement and its impact on the reading interest of fifth-grade students at SD Negeri 1 Ketangga Jeraeng. The research focused on three aspects: the implementation of GLS, the forms of GLS activities that enhance students’ reading interest, and the profile of students’ reading interest as an outcome of the School Literacy Movement implementation. This study employed a qualitative approach with a descriptive research design. The research subjects consisted of the principal, the fifth-grade teacher, and fifth-grade students of SD Negeri 1 Ketangga Jeraeng. Data were collected through observation, interviews, question, and documentation. The data were analyzed using the Miles and Huberman model, which includes data condensation, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation. The findings revealed that the implementation of the School Literacy Movement at SD Negeri 1 Ketangga Jeraeng had been carried out effectively. This was evidenced by the availability of reading corners, diverse reading materials, a literacy-supportive classroom environment, the routine 15-minute reading activity before lessons, and students’ enthusiasm and concentration during reading activities. The School Literacy Movement activities that contributed to improving students’ reading interest included the 15-minute reading habit, the use of reading corners and the school library, and the provision of various reading materials suited to students’ interests. Furthermore, the students’ reading interest profile demonstrated positive outcomes, including enjoyment of reading activities, increased reading habits, interest in diverse types of reading materials, and active participation in literacy activities. Therefore, the School Literacy Movement plays a significant role in fostering and enhancing the reading interest of fifth-grade students at SD Negeri 1 Ketangga Jeraeng.